Anatomical variations of sphenoid sinus among patients undergoing computed tomography of paranasal sinus - Singh, Bhanu Pratap; Metgudmath, Rajendra Basayya; Singh, Divya; Saxena, Udit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The approach to sphenoid sinus still remains a clinical challenge, despite the arrival of endoscopy, computed tomography (CT) and functional endoscopic sinus surgery (FESS). The complex and variable anatomy of the sphenoid sinus can be difficult to appreciate with standard axial or coronal CT images of the sinus. The study was done with the objective to study the anatomy of the sphenoid sinus and its variations, and to compare the prevalence of variants obtained in our study with the reported cases in the literature. Methods: The CT scans of 168 normal slides obtained from 84 patients with paranasal sinus were analysed using triplanar imaging provided by 64-slice spiral CT. The prevalence of each of the sphenoid sinus variation was also analysed. Results: Results showed that the prevalence of pneumatization of the anterior clinoid process, greater wing of the sphenoid, and the pterygoid process was 17.85%, 22.61% and 32.14%, respectively. Protrusion of the internal carotid artery, optic nerve, maxillary nerve, and the vidian nerve was 47.61%, 36.90%, 25% and 26.19%, respectively. Dehiscence of internal carotid artery, optic nerve, maxillary nerve, and the vidian nerve was 30.95%, 29.76%, 14.28% and 22.61%, respectively. The prevalence of pneumatization in the Onodi cells was seen in 17.85% of the cases. Association of septa with an internal carotid artery was seen in 29.7% of the cases. Septa attachment to the optic nerve was also observed in 27.3% of the cases. Conclusions: The triplanar imaging (section thickness of 1 mm) is a better three-dimensional image of the sphenoid sinus, compared to coronal imaging. Triplanar imaging guides the surgical approach of the sphenoid sinus with mentally reconstructed three-dimensional images.